Dermoscopy of atypical pigmented lesions of the face: Variation according to facial areas - Tognetti, Linda; Cartocci, Alessandra; Cinotti, Elisa; D'Onghia, Martina; Żychowska, Magdalena; Moscarella, Elvira; Dika, Emi; Farnetani, Francesca; Guida, Stefania; Paoli, John; Lallas, Aimilios; Tiodorovic, Danica; et al. (Experimental dermatology, 2023)
Atypical pigmented facial lesions (aPFLs)—including lentigo maligna (LM) and lentigo maligna melanoma (LMM), solar lentigo (SL), pigmented actinic keratosis (PAK), atypical nevi (AN), seborrheic keratosis (SK) and lichen planus‐like keratosis (LPLK)—can exhibit clinical and dermoscopic overlapping features. We aimed to investigate if and how 14 dermoscopic features suggestive for the aforementioned aPFLs vary according to six facial sites among 1197 aPFLs cases (excised to rule out malignancy) along with lesion and patients' metadata. According to distribution and association analysis, aPFLs on the forehead of a male patient aged > 69 years displaying the obliterated follicular openings pattern, appear to be more at risk of malignancy. Of converse, aPFLs of the orbital/cheek/nose area with evident and regular follicular openings with diameter < 10 mm in a female aged below 68 are probably benign. The obliterated follicular openings, keratin plugs, evident and regular follicular openings and target‐like pattern features differed significantly among six facial areas in all aPFLs cases. Lesion of the nose may show both features suggestive of malignancy and benignity (e.g. many SL and PAK may display target‐like pattern and some LM/LMM cases display keratin plugs and evident and follicular openings), making these features less specific.